A VIVÊNCIA DA FAMÍLIA NA ABORDAGEM PALIATIVA PARA IDOSOS EM UNIDADE DE TERAPIA INTENSIVA: UM ESTUDO FENOMENOLÓGICO - Rosa, Ana Lídia Emerick (2019)
Population aging associated with the increase of chronic non-communicable diseases affects directly the quality of life of the elderly who experience constant functional changes and frequent hospitalization needs. However, even in the face of technological advances in healthcare, the end-of-life process has been permeated by suffering, isolation and lack of autonomy. The Palliative Care approach gains prominence and relevance in this context, as it seeks to understand death as a natural process within the life cycle and aims to provide a process of death and die with dignity, respect and autonomy to the patient and their families. The objective of this research was to describe an experience lived in the decision-making process in Palliative Care. Semi-structured interviews were conducted with family members of five elderly in terminally ill conditions in the ICU. The analysis of the content of the interviews was performed using thephenomenological approach proposed by Amedeo Giorgi (1985), which resulted in four units of meaning: positive feelings, negative feelings, coping mechanisms and communication. Family experience in the terminally ill process of hospitalized elderly requires effective communication with professionals, reception and respect for the specific demands of each patient and family, encouragement of coping mechanisms during the death process and maintenance of autonomy and dignity of elderly sick and his family.